2019
DOI: 10.3390/jmmp3010008
|View full text |Cite
|
Sign up to set email alerts
|

The Joint Properties of 5754 Aluminium Alloy by Friction Stir Spot Welding

Abstract: In this study, AA5754 sheet samples joined by using a friction stir spot welding method using different rotational speed parameters has been analyzed experimentally. During the experiments, rotational speed of the tool was changed while other process parameters and the tool geometry were kept constant. The effect of tool rotational speed on the hardness values, macrostructure, and tensile properties of joints has been investigated and the results of the experiments show the best tensile shear strength and hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…All three precipitation-hardening alloys had similar grain sizes in their nugget zones after being cooled in water [21]. Macroscopic examination of the fractured samples showed that all of the failures were caused by nugget pull-out [22]. T-joints using friction stir welding (FSW) were developed by process optimization using poly methyl methacrylate (PMMA) and AA5754 alloy [23].…”
Section: Introductionmentioning
confidence: 99%
“…All three precipitation-hardening alloys had similar grain sizes in their nugget zones after being cooled in water [21]. Macroscopic examination of the fractured samples showed that all of the failures were caused by nugget pull-out [22]. T-joints using friction stir welding (FSW) were developed by process optimization using poly methyl methacrylate (PMMA) and AA5754 alloy [23].…”
Section: Introductionmentioning
confidence: 99%
“…Materials of lightweight such as aluminum, however, have apparent advantages more than steel with similar properties but the density is almost lowered three times, significant resistance of corrosion and high level of usage of 85-95%. Al alloys are promising applicants to replace equivalent steel assemblies and their use in automotive manufacturing has lately increased [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…To join Al alloys, in 1991 TWI (Abington, UK) developed a new solid state joining method called FSSW. This newly method of joining is beneficial in the production of Al joints without porosity, contamination, cracks and holes [1].…”
Section: Introductionmentioning
confidence: 99%